SISTEM ELEKTRONIK DATA INTERCHANGE DALAM KOMUNIKASI AWAK KAPAL TUGBOAT PATRA TUNDA 3001 - DEDENG WAHYU EDI; ROHMAT ARIYONO (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2015)
Technology developments, particularly in the services sectors, continue to grow along with the advancing of time. The implementation of electronic data interchange system at PT Pertamina Trans Continental is so helpful for Tugboat crew Patra Tunda 3001 to communicate. Using qualitative descriptive methods and data analysis techniques with simple linear regression analysis, correlation coefficient analysis, determinant coefficient analysis and hypothesis testing, it turns out that a linear regression line equation showed Y = 24.851 + 0.421 X. It means that there is an increase of one unit from each variable in the use of the system "Electronic Data Interchange" (X). It will affect the improvement of crew communication variables (Y) of 0.421 units at constant point of 24.851. The correlation coefficient analysis shows r scors = 0.619 due to the large r between 0.60 to 0.799 which means the relationship between the use of the system "Electronic Data Interchange" and the crew is strong. Determinant coefficient analysis showed the value of Kp = 38.3% which means the effect of the use of the system "Electronic Data Interchange" accounted for 38.3% of the crew communication. Hypothesis test showed that the value of t is 4.176 and the value ttabel is 1.701. Because tcount is more than ttable (4.176 > 1.701), it means Ho is rejected and Ha is accepted. From this result, there is a significant relation between the use of the system "Electronic Data Interchange" and TB Tunda Patra 3001 crew communications.